STOCK MARKET RETURNS DAN FAKTOR YANG MEMPENGARUHI - ZAHRA DINIA; FRISKA FIRNANTI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study is to obtain empirical evidence about the factors that influence stock market returns. The examined factors are market capitalization, earnings per share, debt to equity ratio, return on equity, price earnings ratio, and operating leverage. Samples in this research are manufacturing companies listed in Indonesia Stock Exchange during 2013-2015. Samples were obtained through purposive sampling method and the data were analyzed using multiple regression analysis. The results show that return on equity have influence towards stock market returns. However, market capitalization, earnings per share, debt to equity ratio, price earnings ratio, and operating leverage don’t have any influence toward stock market returns.